Pengaruh Diskon Flash Sale Dan Gratis Ongkir Terhadap Impulse Buying Melalui Media Sosial Tiktok Pada Mahasiswa Manajemen Upi ”Yptk” Padang Angkatan 2022 - Putri Aprilliany; Emil Salimi; Della Asmaria Putri (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of flash sale discounts and free shipping promotions on impulse buying through TikTok social media among Management students of UPI